Seasonally Evolving Impacts of Multiyear La Niña on Precipitation in Southern China - Huang, Guansheng; Wang, Run; Liu, Jingpeng; Gao, Li; Liu, Minghong; Chen, Quanliang (Frontiers in Earth Science, 2022)
The multiyear La Niña (MYLN) is characterized by longer duration, bimodal feature, more continuous circulation anomaly, and different climate impacts compared to the canonical single-peak La Niña. In this study, we focus on the evolving impacts of the MYLN on precipitation in southern China, which mainly occur in boreal winter and summer and correspond to significantly less precipitation and frequency of extreme rainfall. Results show that such impacts have remarkable differences between the first and second half of the MYLN lifecycle. In the first boreal winter when the MYLN reaches its first peak, the precipitation in southern China decreases significantly, while it tends to be insignificantly anomalous in the next winter. In the summer after its first peak, the MYLN has no apparent impact on precipitation in southern China, but when it basically disappears in the next summer, precipitation decreases significantly in southern China. Such seasonally evolving features in the impacts of the MYLN on precipitation in southern China can be mainly interpreted by the patterns of the anomalous cyclonic circulation in northwestern subtropical Pacific during the first peak winter and the decaying summer of the MYLN, which favors an anomalous reduction of moisture supply over southern China.